Guidance and Counseling Services to Develop Student Career Maturity - Mafufah Hastin; Najlatun Naqiyah; Eko Darminto (IJORER : International Journal of Recent Educational Research, 2022)
This study describes career guidance and counseling services for career maturity of high school students. The method used is library research method. The results of the study refer to the components of international, national journal articles and input from supervisors, namely: The successful application of services from 25 journals has 6 studies that are influenced by various factors (a) adversity quotient, self-awareness, gender and socioeconomic status, (b) learning motivation, (c) locus of control and self-concept, (d) self management. 11 studies of career maturity results can improve. Three studies on the use of media, namely assessment tools, modules and multimedia. Three studies through self-efficacy, 2 studies compare the career maturity of students between boys and girls. Methods or techniques found 8 methods or techniques, namely (a) group counseling services, (b) career portfolio media, (c) career information services, (d) self management techniques, (e) collaborative career guidance, (f) interactive multimedia career information, (g) self-efficacy techniques, (h) career guidance module. The scope and targets are from higher education to high school. The targets are mostly mixed sex, both individually and collectively. Suggestions or recommendations that are expected to provide career guidance services to increase student career maturity.